2019
DOI: 10.1186/s13049-019-0645-z
|View full text |Cite
|
Sign up to set email alerts
|

Spinal injury in alpine winter sports: a review

Abstract: Introduction Alpine winter sports have become increasingly popular over recent decades, with a similar increase in accident incidence. This review provides an overview of the most recent literature concerning spinal injury epidemiology, mechanisms, patterns and prevention strategies in the context of alpine winter sports. Material and methods The PubMed, Cochrane Library, and EMBASE databases were searched using the keywords spine injury, alpine injury, spine fracture, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
0
12
1
Order By: Relevance
“…Concerning prevention, few studies analyzed the effectiveness of helmet use, airbags, back guards, multichambered foams or finger-tapping, especially in sports like climbing, paragliding, skydiving and base jumping. In contrast to alpine winter sports, where 12 meta-analyses have shown that wearing a helmet significantly reduces the risk of head injuries [ 83 ], in mountain biking there is still some controversy regarding the benefit of helmet use [ 17 , 21 ]. The interplay between the safety conferred by the safety device versus a false sense of security potentially influencing risk-taking behaviour would be particularly interesting.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning prevention, few studies analyzed the effectiveness of helmet use, airbags, back guards, multichambered foams or finger-tapping, especially in sports like climbing, paragliding, skydiving and base jumping. In contrast to alpine winter sports, where 12 meta-analyses have shown that wearing a helmet significantly reduces the risk of head injuries [ 83 ], in mountain biking there is still some controversy regarding the benefit of helmet use [ 17 , 21 ]. The interplay between the safety conferred by the safety device versus a false sense of security potentially influencing risk-taking behaviour would be particularly interesting.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of alpine winter sports and spine trauma yielded 64 studies. 35 Skiing, snowboarding, and tobogganing are the reasons for falls. The thoracolumbar spine is the most common region for spinal injury.…”
Section: Sports Injuriesmentioning
confidence: 99%
“…Disc injuries seem to occur more commonly in alpine winter sports athletes than in the general population. 35 A study from Switzerland examined the trauma cases due to extreme sports in Swiss Alpines. 36 A total of 616 patients rescued with helicopters for a ten-year interval (1998-2008) were examined.…”
Section: Sports Injuriesmentioning
confidence: 99%
“…helmet, rope, belaying) and the activity. For instance, critical injuries in climbing often involve the pelvis and chest [7], canyoning accidents the lower and upper extremities [8], and mountain biking, winter, and aviation sport injuries the head and thoracolumbar vertebral column [9][10][11].…”
Section: Injury Patterns Of Patients With Multiple Trauma In the Mounmentioning
confidence: 99%